New concepts on chronic mountain sickness - Zubieta-Castillo, G.; Zubieta-Calleja , G. (Acta Andina, 2025)
The adaptation capacity of human beings to atmospheric pressure changes is remarkable. In high altitude adaptation (HAA) we should consider: that of normal man and that of the diseased. The acute HAA can be more dramatic and problematic than chronic HAA. The diseased are the same as those at sea level and have hypoxic physiognomies. The term Chronic Mountain Sickness (CMS), has created confusion, because it includes pulmonary diseases that cause Excessive Erythrocytosis (EE). EE, is a mechanism of adaptation that increases the oxygen carrying capacity of the blood by increasing the number of red blood cells. The term1 "dysadaptation to high altitude", for CMS patients that present with EE, seems inappropriate and does not provide a pathogenesis. Above 3000 m, in the Bolivian Andes. respiratory disease with EE affects thousand of persons. With the availability of pulmonary function tests and blood gas techniques, it is increasingly evident thar EE is due to some ventilarory or respiratory alteration. Patients with EE show aberrations of one or more of the following: FVC; FEV.1/FVC;FEF 25-75%. Alveolar ventilation; PaCO2; pulmonary shunts; uneven ventilation; TLC; CC/TLC; CV/VC; blood pressure; or chest x-ray. All of our patients had a PaCO2 below 56 mmHg. In patients with EE there is a tendency for the hemarocrit to increase with age (r = 0.35) with a plateau at around 60 years of age. We found an inverse relalionship between FVC (r = 0.45) and RV/TLC (r = 0.10) with the hematocrit. In conclusion, EE (appearing as CMS) is an adaptation to hypoxia caused by disease at high altitude.